Perancangan Website Kecamatan Pasar Rebo Menggunakan Framework Bootstrap - Mega Wahyu Rhamadani; Herry Wahyono; Nuke L Chusna; Nur Hikmah; M.Ageng Laksono (Yayasan Literasi Sains Indonesia, 2023)
The Pasar Rebo website is a public publication tool that provides information and an overview of Pasar Rebo, as well as enhancing services to the public to access information. Through this website, it is hoped that the community can obtain all information about the Pasar Rebo subdistrictThe website is no longer limited to providing static information, but is also capable of providing dynamic information by connecting to a database. Community Service activities are carried out in the Pasar Rebo sub-district. From the results of interviews with sub-district officers in Pasar Rebo, so far the community has only been limited to getting information on services, the one million orchid village program, facilities and infrastructure at the Pasar Rebo sub-district manually. Bootstrap is one of the most popular CSS (Cascading Style Sheet) frameworks used to build a website's frontend. By using Bootstrap, developers can speed up the web appearance development process because they no longer need to create styling from scratch, and ensure that the web appearance that is built is responsive and easy to read on various devices (desktop, tablet, or mobile). Therefore, the Pasar Rebo sub-district website was designed using a bootstrap framework with the aim that the public can easily access up-to-date information in the Pasar Rebo sub-district anytime and anywhere.